COVID-19 EFFECT IN SOCIETY AND GOVERMENT - Muhammmad Supriyadi; Danisa Salsabila; Sephiala Riztianendra (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2020)
In indonesia, the underlying cause is a government that is seen as sluggish and ill-advisedin dealing with the corona epidemic. Government policy to implement a lockdown system leads tocritics or deals with "lockdown - quarantine". The fundamental problem of discovery concerns thelack of data and information on covid 19 because of noncentered sources of information andmoreover does the government avoid responsibility to ensure the survival or basic needs of thepeople if quarantine policies are applied. Some residents ignore demand by governments to keeptheir distance from social distance, engaging in daily routines and activities despite realizing thegreater risk of exposure to or transmitting a virus. Government policies on social distance seemto be less effective because they clash with the cultural norms and social behaviors of people. Asollution to the problem is society should be educated and facilitated when social distancedpolicies, work from home or whatever form of plague treatment is implemented. This time will bea moment for the people to help each other.